Developmental arborization of sensory neurons in the leech Haementeria ghilianii. I. Origin of natural variations in the branching pattern - Kramer, AP (J Neurosci, 1985)
The overall sizes, contours, and positions of the receptive fields maintained by different individual cells of the T, P, and N types of mechanosensory neurons in the segmental skin of the leech Haementeria ghilianii are not subject to wide variation. However, the locations and contours of the boundaries which separate the various compartments of the sensory field, namely, the major and minor fields, as well as their component subfields, do vary significantly. These variations are reflected in differences in the detailed pattern of arborization of the mechanosensory axon branches that innervate different parts of the receptive field. The appreciable variation in the kinetics of embryonic outgrowth of sensory axon branches, in conjunction with a mechanism of neuronal self-avoidance, is a probable source of this variability in adult receptive field structure. Thus, establishment of these sensory field components would seem to entail a first-come-first-served territorial exclusion between different axon branches extended by the same neuron.